Ріст і розвиток бджолиних сімей користувальної групи у разі стимулюючої підгодівлі - Кучер, С. О.; Kucher, S. O.; Пастушок, Р. С.; Pastushok, R. S.; Милостивий, Роман Васильович; Mylostyvyi, Roman; Milostiviy, Roman; Milostivyiy, Roman; Mylostyvyi, R. V.; Mylostyvyi, Roman V.; Mylostyvy, R.; Mylostyvyi, R.; et al. (ННЦ «Ін-т бджільництва ім. П.І. Прокоповича» НААН України ; Ін-т біології тварин НААН України, 2024)
У статті представлені дослідження щодо впливу різних видів підгодівлі на ріст і розвиток бджолиних сімей. Як підгодівлю для контрольної групи використовували цукровий сироп та пасту «Канді» для дослідної групи. Показано, що бджоли, які отримували глюкозо-цукровий сироп та пудру у пасті «Канді», мали більші показники сили бджолиної сім’ї (14,6 вуличок проти 9,5 вуличок у контролі). Також у дослідній групі був більшим показник рівня та темпу вигодовування. Таким чином, застосування пасти «Канді» мало більший ефект порівняно з цукровим сиропом. Introduction. Artificial breeding of queen bees involves the use of different categories of bee families. Various types of feeding are used to stimulate bee colonies. The goal of the work is to investigate the growth and development of bee families of the user group using stimulating feeding. Materials and methods of research. The research was conducted on bee colonies of the Ukrainian steppe breed, which were kept in 16 frame beehives. 3 groups of analogue families were formed, from maternal and paternal families, and from families of caregivers. By the time the control and experimental groups were formed, the bee families had 2.5 kg of bees, 8.0 kg of fodder honey, a queen at the age of 18 months, sealed brood in 2 frames (160 squares) and 2 frames with open brood. Bees were fed with sugar syrup (control group) and “Candy” paste (experimental group). The number of brood and the strength of bee families were determined. Results of research and discussion. In the control group, the strength of families reached 9.5 streets, in the experimental group – 14.6 streets. When feeding “Candi” the strength of families increased by 2.08 times, when feeding with sugar syrup – by 1.35 times. The level of brood feeding in the control group was 110 squares, in the experimental group – 112 squares. Compared to the initial value, the feeding rate of the brood after feeding with sugar syrup increased by 2.45 times, when feeding “Kandi” – by 2.89 times, respectively. By the end of the observation period, this indicator was 270 squares in the control group, 324 squares in the experimental group. Conclusions and prospects for further research. With the use of “Candy” paste, indicators of the strength of bee colonies and the production of brood are higher than when feeding bees with sugar syrup.
Growth and development of bee families of the user group under stimulating nutrition
Милостивий Роман Васильович https://orcid.org/0000-0002-4450-8813
Keywords: вигодовування розплоду; brood feeding; продуктивність; productivity; бджільництво; beekeeping; стимулююча підгодівля; stimulating feeding; бджолина сім’я; bee colony